Shallow-water species of the genus Aplidium (Ascidiacea) from Kamchatka and Commander Islands - Sanamyan, Karen; Sanamyan, Nadya (Zootaxa, 2011)
Four shallow-water colonial ascidians of the genus Aplidium (Aplousobranhia: Polyclinidae) are identified in the material collected by SCUBA divers off the coast of East Kamchatka and Commander Islands. Three species from Kamchatka were previously known from this region but were wrongly identified and two of them (A. dissectum n. sp. and A. eborinum n. sp.) are now redescribed as new species. Aplidium redikorzevi nom nov. (for Amaroucium fragile Redikorzev, 1927) is recorded on Commander Islands first time from its original description.